KUALITAS PELAYANAN TERHADAP KEPUASAN PROGRAM IN HOUSE TRAINING PADA LPMA-STMA TRISAKTI MENGGUNAKAN METODE SERVQUAL - Robidi, Robidi; Bayu Widjiaji; Syahrial Sidik; Ferianis Lature (Bajang Institute, 2025)
This study aims to analyze the quality of service in the In-House Training (IHT) program at LPMA-STMA Trisakti using the SERVQUAL method and measure its impact on participant satisfaction. This method evaluates five dimensions of service quality—reliability, responsiveness, assurance, tangibles, and empathy—and identifies gaps between expectations and service performance. The results showed that overall, service quality was close to participants' expectations, with an average gap value of -0.036. The Tangibles and Empathy dimensions had the largest gaps, indicating a need for improvement in physical facilities and a more personalized approach to participants. Importance Performance Analysis (IPA) identified areas that need priority improvement, particularly in terms of training facilities and facilitator responsiveness. This study concludes that LPMA-STMA Trisakti needs to improve these aspects to improve service quality and overall participant satisfaction. The contribution of this research is expected to provide practical insights for LPMA-STMA Trisakti in improving training services in the future